Invasive pneumococcal disease confirmed in five different sites including Austrian syndrome in a male patient with methamphetamine abuse - Mekraksakit, Poemlarp (BMJ Case Rep, 2020)
A 60-year-old man with no significant medical history was found unresponsive by his neighbour; he had neck stiffness on physical examination in the emergency department. He later developed acute hypoxic respiratory failure requiring endotracheal intubation. He is a binge drinker on weekends, and methamphetamine was detected in his urine. Contrast-enhanced CT of the chest, abdomen and pelvis revealed multifocal pneumonia, bilateral psoas abscesses and right infraspinatus muscle abscess. Blood, sputum and cerebrospinal fluid cultures grew Streptococcus pneumoniae. Transthoracic echocardiography (TTE) revealed tricuspid endocarditis with mild valve insufficiency. He was initially treated with intravenous antibiotics and underwent incision and drainage of right psoas abscess. However, he still had recurrent fever and confusion. Repeat TTE showed larger vegetation, and he also developed septic emboli at the posterior basal right lower lobe pulmonary artery. The patient underwent tricuspid valve debridement and was finally discharged after completing 6 weeks of intravenous antibiotic treatment.